2017
DOI: 10.1016/j.molcel.2016.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-Dependent Feedback Inhibition of RIG-I by DAPK1 Identified by Kinome-wide siRNA Screening

Abstract: Cell-autonomous induction of type I interferon must be stringently regulated. Rapid induction is key to control virus infection, whereas proper limitation of signaling is essential to prevent immunopathology and autoimmune disease. Using unbiased kinome-wide RNAi screening followed by thorough validation, we identified 22 factors that regulate RIG-I/IRF3 signaling activity. We describe a negative-feedback mechanism targeting RIG-I activity, which is mediated by death associated protein kinase 1 (DAPK1). RIG-I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 61 publications
(73 reference statements)
1
47
0
2
Order By: Relevance
“…These data suggest that PPP6C acts as a positive feedback regulator by dephosphorylating RIG-I. A recent study revealed a negative feedback mechanism of DAPK1 in RIG-I phosphorylation after RIG-I activation (Willemsen et al, 2017). To demonstrate a potential feedback role of PPP6C, we examined the RIG-I S8 phosphorylation status at early and later time points during RIG-I activation in WT, PP1 KO, and PPP6C KO cells infected with VSV.…”
Section: Ppp6c Is Responsible For Rig-i Dephosphorylationmentioning
confidence: 84%
See 1 more Smart Citation
“…These data suggest that PPP6C acts as a positive feedback regulator by dephosphorylating RIG-I. A recent study revealed a negative feedback mechanism of DAPK1 in RIG-I phosphorylation after RIG-I activation (Willemsen et al, 2017). To demonstrate a potential feedback role of PPP6C, we examined the RIG-I S8 phosphorylation status at early and later time points during RIG-I activation in WT, PP1 KO, and PPP6C KO cells infected with VSV.…”
Section: Ppp6c Is Responsible For Rig-i Dephosphorylationmentioning
confidence: 84%
“…Serving as an auto-inhibitory mechanism, the N terminus of RIG-I is highly phosphorylated by protein kinase C (PKC) (Maharaj et al, 2012). RIG-I can be activated by PP1a or PP1g through dephosphorylation after RNA binding, which can be suppressed again through feedback-induced phosphorylation by DAPK1 (Willemsen et al, 2017). Thus, the S8 and T170 phosphorylation status is regulated by dynamic regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The primary screening was performed by reverse transfection cell arrays with a human siRNA kinome library as described elsewhere (Erfle et al, 2007;Willemsen et al, 2017;Reiss et al, 2011). This library targets all known and predicted 719 human kinases with three individual siRNAs per gene (Silencerâ Human Kinase siRNA Library V3, AM80010V3; Ambion, ThermoFischer Scientific).…”
Section: Contact For Reagent and Resource Sharingmentioning
confidence: 99%
“…RNA isolation from cell lysates, reverse transcription and quantitative real-time PCR were performed as described in [59]. Briefly, 1 µg of isolated whole cell RNA was reverse-transcribed with random hexamer primers and gene expression levels were assessed with gene-specific primers and SYBR ® Green (Bio-Rad, Feldkirchen, Germany).…”
Section: Rna Isolation Reverse Transcription and Qrt-pcrmentioning
confidence: 99%
“…Cell lines stably overexpressing putative HCV host factors were generated as described in [59]. Briefly, lentiviral particles were produced in HEK293T cells [66] by calcium phosphate transfection and used for transduction of target cells.…”
Section: Generation Of Stable Overexpressing Cell Linesmentioning
confidence: 99%